Analysis of Echocardiography Images Using Grid Independent Technique for Patients with Mitral Valve Problems (MVP) - Mohd Azrul Hisham, Mohd Adib (2011)

(untitled)
With echocardiography images collected by a transthoracic transducer, can be used to evaluate the mitral valve problems. Incorrect surgical of mitral valves failure will cause death and the surgical repair can be improved by knowing the correlations between backflow and the rigidity of mitral valve. In this study, a nearly method for identifying the mitral valve rigidity from two-dimensional (2D) images of echocardiography is presented. This method employs the grid independent technique. Systolic and diastolic stages of mitral valve condition were investigated by 10 patients with MVP. The results show linear correlation between degeneration of the valves and volume of backflow. The findings are the prediction of the behavior of the mitral valves and blood flow which can assist the medical practitioners in their decision on the patients’ treatments.